Formation of the Key Professional-pedagogical competencies of the teacher in modern conditions - Amangul Orakova, Kulzada Kudaibergeneva,; Sibagatova Gulnar, Kymbat Akhmetova, Lyudmila Sainova, (Opción, 2019)
The article aims to investigate the formation of the Key Professional-pedagogical competencies of the teacher in modern conditions via different methods such as pilot conversation, interview, surveys, pedagogical observation, educational tasks and using the method of linear correlations. As a result, the formation of professional-pedagogical competencies requires the organization of the educational process, in which, instead of transmitting of knowledge from teacher to student, a new format of the subject-subject interaction will be introduced. As a conclusion, the formation of the key professional-pedagogical competencies furthers the improving of the level of pedagogical work and quality of modern education.